Label-free electrochemical multi-sites recognition of G-rich DNA using multi-walled carbon nanotubes–supported molecularly imprinted polymer with guanine sites of DNA. (1st May 2016) - You, Min; Yang, Shuai; Jiao, Fang; Yang, Li-zhu; Zhang, Fan; He, Pin-Gang
Graphical abstract: Highlights: A novel label-free electrochemical multi-sites recognition strategy of G-rich DNA was designed and MWCNTs-MIP with guanine recognition sites of DNA was employed as the recognition material. Under the optimized experimental conditions, MWCNTs-MIP presented high selectivity for G-rich DNA and the imprinting factor of this composite was nearly 5.68. A wider linear range (0.05–1 μM and 5–30 μM, respectively) and a higher sensitivity (detection limit: 7.52 nM, S/N = 3) was realized in the detection of G-rich DNA by the MWCNTs-MIP. Abstract: A novel label-free electrochemical strategy was designed for multi-sites recognizing the guanine-rich DNA (G-rich DNA) with surface molecular imprinting polymer composite, in which the multi-walled carbon nanotubes (MWNCTs) were regarded as supporting material and the molecularly imprinted polymer (MIP) with guanine sites of DNA was applied as recognition element. Firstly, the vinyl groups were grafted onto the surface of carboxylic acid-functionalized MWNCTs (MWCNTs-COOH) through chemical modification. Then, the composite of MWCNTs-MIP was fabricated by the selective copolymerization of methacrylic acid, ethylene glycol dimethacrylate and guanine on the vinyl group-functionalized MWNTs surface. MWCNTs-MIP was characterized by different techniques, including Fourier transform infrared (FTIR) spectroscopy, scanning electronic microscopy (SEM), cyclic voltammogram (CV) and electrochemical impedance spectroscopy (EIS), showing that the MWCNTs-MIP composite was successfully prepared. Under the optimized conditions, the imprinting factor was nearly 5.68 according to the comparative slopes obtained on MWCNT-MIP and MWCNTs-non-imprinted polymer (MWCNTs-NIP), indicating that MWCNTs-MIP exhibited high selectivity for G-rich DNA. Moreover, the MWCNTs-MIP composite had a relatively wide linear range over G-rich DNA concentration of 0.05–1 μM and 5–30 μM with a detection limit of 7.52 nM (S/N = 3). Furthermore, the novel electrochemical strategy based on imprinted composite has very excellent performance in real samples of human serum and human urine.